Agricultural Adaptation to Drought for Different Cropping Systems in Southern China under Climate Change. (5th June 2019) - Zhao, Junfang; Lu, Houquan; Li, Yijun
Abstract: This study investigates agricultural adaptation to drought for different cropping systems in southern China. The study area was divided into three regions: South China (SC), South of the Yangtze River (SYR), and Southwest China (SWC). An index of agricultural adaptation to drought ( D ) was established. Our findings indicated that the average total crop water demand varied greatly among the regions from 1961 to 2010 in southern China. The maximum value was found in the SC region, followed by the SYR and SWC regions. The effects of droughts on different crops were noticeable. Frequent droughts were recorded in late rice than in early rice in the SC and SYR regions. Droughts in the SWC region mainly affected winter wheat. Moreover, the effects of droughts on crops varied during different growth stages. More frequent and serious droughts occurred during the crop critical flowering stage. Particularly, the frequency of moderate and severe droughts for late rice in the SYR region was 62% during the critical flowering stage. For the SC and SYR regions, the D values of early rice (0.29 and 0.29) were lower than that of late rice (0.31 and 0.33), respectively. For the SWC region, the D values of winter wheat and rice were both low, with averages of 0.16 and 0.29, respectively. Our study provides interesting insights for improving the drought defense abilities for different cropping systems by changing crop planting proportion on a regional scale in China. Abstract : Research Impact Statement : Agricultural adaptation to drought for different cropping systems can be estimated based on sown area, actual yield, water demand, and potential evapotranspiration of crop in southern China.